Provision of Creative Teaching Materials in Improving Creative Disposition and Creative Thinking Skills of High School Students - AA Sukarso; I Putu Artayasa; Syamsul Bahri; Afriana Azizah (Postgraduate, University of Mataram, 2022)
This study examines the use of creative teaching materials in building students' creative thinking skills. The research sample was 53 students of class X one of the public high schools in Mataram. Instruments for learning activities include creative teaching materials modified by the Writing to Teach approach, student books, and data collection instruments. Creative dispositions were measured using closed questionnaires on curious, persistent, imaginative, collaborative, and disciplined aspects. Students' creative thinking skills were measured using a creative thinking skills test in the form of five essay questions on viruses. The results of the study show that the use of creative teaching materials triggers creative dispositions in the five aspects of inquisitive, persistent, imaginative, collaborative, and disciplined aspects, and also improves creative thinking skills where the average score of classes using creative teaching materials is higher than the average score in classes using books student package. Students' creative thinking skills improve in all aspects of creative thinking skills (flexibility, fluency, elaboration, and originality). This shows that the use of creative teaching materials provides better conditions for the development of student's creative thinking skills.